Diversity of Endophytic Fungi from Lime Plants (Citrus aurantifolia, Swingle) - Riza Umami; Ummi Hiras Habisukan; Kurratul A’ini (Universitas Nusa Bangsa, 2023)
Lime (Citrus aurantifolia, Swingle) is a plant with medicinal properties. This plant is needed on a large scale to produce biomass. Medicinal plants with decreasing numbers and populations can be developed through scientific technology by isolating endophytic fungi. Endophytic fungi are microorganisms that are found in plant tissues without causing damage to their host plants. This study uses the exploratory method, namely searching and finding. The purpose of this study was to identify endophytic fungi in lime plants. The study's results obtained ten isolates of endophytic fungi from different plant organs (leaves, stems, bark, roots, fruits). Endophytic fungi were identified through macroscopic and microscopic characteristics and then compared with an identification book of endophytic fungi. Eight genera were found, including Beltrania and Nigrospora on leaves, Fusarium and Chaetomium on fruit, Pythium on stems and bark, Paecilomyces on bark, Mucor and Mortierella on roots.